TYPES OF TRANSLATION (Archive of Conferences, 2021)
Though the basic characteristics of translation can be observed in all translation events, different types of translation can be singled out depending on the predominant communicative function of the source text or the form of speech involved in the translation process. Thus, we can distinguish between literary and informative translation, on the one hand, and between written and oral translation (or interpretation), on the other hand1 . Literary translation deals with literary texts, i. e. works of fiction or poetry whose main function is to make an emotional or aesthetic impression upon the reader. Their communicative value depends, first and foremost, on their artistic quality and the translator's primary task is to reproduce this quality in translation